CONGENITAL MALFORMATIONS OF THE CENTRAL NERVOUS SYSTEM AMONG NEWBORNS DELIVERED AT TERTIARY HEALTH CARE HOSPITAL IN INDIA: A CROSS-SECTIONAL STUDY - Devaliya, Sangeeta; Tomar, Shashi Prabha; Gupta, Preeti; Soni, Vaishali (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Background: Malformations of the central nervous system (CNS) are a significant contributor to childhood morbidity and death. Congenital CNS abnormalities may result in long-term disability that affects not only the child's development and well-being but also families, the medical system, and society as a whole. Purpose: The purpose of this study is to determine the incidence, type, and associated risk factors of CNS malformations in newborns who were delivered to the Obstetrics and Gynecology department of Netaji Subhash Chandra Bose Medical College (NSCB Medical College). Methods: An observational hospital-based study was carried out in the departments of pediatrics and obstetrics and gynecology at the NSCB Medical College and Hospital in Jabalpur. Data was entered into MS Excel, and IBM-SPSS 23.0 was used to perform descriptive and inferential statistical analysis. During a one-year study period, 40 cases of CNS malformation out of 7117 deliveries were found to have occurred either before or after birth. Results: During the study period, 40 cases of CNS malformation out of 7117 deliveries were identified either prenatally or at birth, making an incidence of 0.5%. Of all CNS anomalies, hydrocephalus accounted for 52.5 percent, whereas neural tube defects accounted for 27.5 percent. The other two main CNS abnormalities identified in utero were ventriculomegaly and midline defects. Conclusion: This study identified CNS malformations in newborns, with hydrocephalus and neural tube defects as the most common types. Key risk factors included younger maternal age, rural residence, inadequate antenatal care, adverse obstetric history, chronic illness, polyhydramnios, and maternal addiction.